GLAST regulates glutamate dynamics and interneuron maturation in the developing cortex - Shih, Jennifer. (2018)
Abstract: The astrocytic glutamate transporters GLAST and GLT-1 are highly expressed in the neocortex and are critical for regulation of extracellular glutamate concentrations. Glutamate, in turn, regulates many aspects of postnatal cortical development. However, the relative contributions and functional roles of GLAST and GLT-1 in the developing postnatal cortex are not well understood. The main goal of this dissertation is to test the hypothesis that astrocytic glutamate transporters contribute to postnatal cortical circuit development. To test this hypothesis, I used heterozygous mouse models where there is 50% reduction of GLAST or GLT-1 protein levels. Using astrocyte glutamate transporter recordings, I show that GLAST is the predominant astrocytic transporter during postnatal cortical development, while GLT-1 becomes dominant in the mature cortex. This functional finding confirms previous studies characterizing GLAST and GLT-1 expression and suggests that GLAST might be critical for the development of cortical circuits. By recording tonic NMDA currents, we show that decreased GLAST function leads to increased ambient glutamate in the developing cortex. Previous work done in the lab had shown that fast-spiking interneurons in the cortex are particularly susceptible to tonic NMDA activation due to their NMDAR subunit composition. Therefore, I tested whether the effects of altered tonic glutamate signaling had cell-type specific effects. Fast-spiking interneurons in the GLAST+/- cortex, but not excitatory pyramidal cells, have altered action potential firing and intrinsic membrane properties during development and altered morphology in the mature somatosensory cortex. Additionally, inhibitory synapse number and interneuron distribution in the cortical layers are altered in the mature GLAST+/- cortex. Finally, I found that the broad deficits in inhibitory circuits correlate with altered slice hyperexcitability in the mature GLAST+/- cortex, suggesting that loss of GLAST function during development leads to loss of inhibitory control of cortical networks. Since the GLT-1+/- cortex was not hyperexcitable at this mature stage, the results suggest that the aberrant cortical network activity observed results from disruptions during development that persist in the GLAST+/- cortex, rather than from deficits in acute glutamate uptake capacity. Taken together, the results from my thesis project indicate that GLAST, specifically, regulates glutamate in the developing neocortex and that its function is critical for the maturation of inhibitory function in cortical circuits. This main finding is in contrast with earlier work done in the thesis highlighting a role for GLT-1 in the acute response to kainic acid-induced seizures.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of Neuroscience.; Advisor: Chris Dulla.; Committee: Michele Jacob, Yongjie Yang, and Janice Naegele.; Keyword: Neurosciences.